Pendekatan Business Model Canvas Sebagai Perancangan Strategi Bisnis Baru: Studi Pada UMKM UD. Gading Mas Pasuruan - Fajar Azmi Kurniawan (Universitas Yudharta Pasuruan, 2017)
English This study aims to design a new strategy based on Business Model Canvas approach. From Business Model Canvas there are nine interconnected elements including, Customer Segments, Value Propositions, Channels, Customer Relationships, Revenue Streams, Key Resources, Key Activities, Key Partnerships, and Cost Structure. The data were collected using interview technique. Analysis method used is SWOT Analysis. In this study, researchers used qualitative research methods. The results of this study show the design of a new strategy of nine elements. Customer Segments UD. Gading Mas by adding Customer Segments, Value Propositions of new product innovations with variations, promotional Channels through print or electronic media, Customer Relationship rewarding to high loyalty customers, Revenue Streams increase to selling price of robusta processed coffee and appropriate pricing for arabica coffee processing, Key Resources improves human resources by training employees, Key Activities production processes effectively and efficiently, Key Partnership is the main partner associated with the product being offered, and Cost Structure finance for promotion. Keywords: Business Model Canvas, SWOT Analysis, New Strategy Indonesia Penelitian ini bertujuan untuk merancang strategi baru berdasarkan pendekatan Business Model Canvas. Dari Business Model Canvas terdapat sembilan elemen yang saling terhubung diantaranya, Customer Segments, Value Propositions, Channels, Customer Relationship, Revenue Streams, Key Resources, Key Activities, Key Partnership, dan Cost Structure. Pengumpulan data dilakukan dengan menggunakan teknik wawancara. Metode Analisis yang digunakan adalah Analisis SWOT. Dalam penelitian ini, peneliti menggunakan metode penelitian kualitatif. Hasil dari penelitian ini menunjukan rancangan strategi baru dari sembilan elemen. Customer Segments UD. Gading Mas dengan menambah Segmen Pelanggan, Value Propositions inovasi produk baru dengan variasi, Channels promosi melalui media cetak ataupun media elektronik, Customer Relationship pemberian hadiah kepada pelanggan yang memiliki loyalitas tinggi, Revenue Streams peningkatan terhadap harga jual kopi olahan jenis robusta dan penetapan harga yang sesuai untuk olahan kopi jenis arabika, Key Resources meningkatkan sumber daya manusia dengan pelatihan terhadap karyawan, Key Activities proses produksi secara efektif dan efisien, key partnership mitra utama yang berhubungan dengan produk yang di tawarkan, dan Cost Structure membiayai untuk promosi. Keywords: Business Model Canvas, Analisis SWOT, Strategi Baru